(untitled) (International Seven Journal of Multidisciplinary, 2023)
Faced with the impacts triggered by one of the biggest pandemics in human history, it was necessary to address this fact so that it is known what is often not shown on television and the internet. Such camouflaged information corresponds from the true origin of the virus to its sequels. The advance of science in “developed” countries and the absence of it in “underdeveloped” countries, expose the current inequality around the world, at the same time that the effects of globalization are felt by all, even if in a harmful way. The denial of science as an obstacle to fighting the virus, in addition to being responsible for frightening numbers of deaths, are also analyzed in this article in order to warn how dangerous and harmful the denial of truth is. The confinement process - already frightening by name - gave rise to jobs that did not exist before, in addition to establishing a new way of life; the same made people develop physical and mental health problems as a result of living in a new prison. Discussions between people about the right way to prevent triggering friendships are also present in the article as a way of showing how fragile relationships are. In addition to showing the frightening numbers of deaths around the world, with Brazil in the sad position of second place. This being the new world scenario, promoting insecurity and uncertainty about the future. DOI: 10.56238/isevmjv2n1-004